Exploring language use in apology strategies of tourists visiting Saudi Arabia. - Abdullah Al Fraidan; Abdulaziz A Alhulaybi (PLoS ONE)
This research explores the apology strategies employed by international tourists visiting Saudi Arabia, particularly in the context of the Kingdom's rapid tourism expansion under Vision 2030. With the introduction of new tourism policies, the country has opened itself to a wide range of international visitors, increasing the likelihood of cultural missteps. The study investigates how tourists navigate Saudi Arabia's conservative social norms, focusing on factors such as language use, cultural awareness, and the perceived severity of offenses. Data were collected through qualitative focus group interviews with international tourists, analyzing how apology strategies are influenced by social dynamics, gender norms, and power structures. The findings suggest that tourists who demonstrate cultural sensitivity, particularly by using Arabic, are more likely to have their apologies accepted. The study highlights the importance of cross-cultural competence in managing tourist-local interactions and provides insights for tourism operators and policymakers on improving the tourist experience in Saudi Arabia. The research contributes to a deeper understanding of cross-cultural communication in the context of a rapidly growing tourism industry.